LIQUIFIED PETROLEUM GAS (LPG) ANALISIS PENGARUH PRODUKSI DAN HARGA TERHADAP EKSPOR LPG DI INDONESIA - Sudijo Sudijo (Fakultas Ekonomi Universitas Borobudur, 2013)
The problem of this research is whether are the influence of production and price to LPG export in Indonesia. The research method is explanatory method using associative and quantitative research. The result of this research showed that the influence of production to LPG export in Indonesia is strong enough (r = 0,574). The influence of price to LPG export in Indonesia is very strong (r= -0,906). The influence of production and price together to LPG export in Indonesia is very strong (l? = 0, 908). l'he influence contribution of production and price to LPG export in Indonesia is 82,5% (R2 = 0,825). Key Words : production, price, export and LPG.